Impact of physical parameterization schemes on the numerical simulation of Orissa Super Cyclone (1999) - TRIVEDI, D. K.; MUKHOPADHYAY , P.; VAIDYA, S. S. (MAUSAM, 2006)
& 29 vDrwcj] 1999 dks mM+hlk esa vk, egkpØokr dks izfr:fir djus ds fy, isuflyosfu;k LVsV ;wfuoflZVh ds jk"Vªh; ok;qeaMyh; vuqla/kku dsUnz ds eslksLdsy ekWMy ¼,e- ,e- 5½ ds xSj&nzoLFkSfrd :ikarj dk mi;ksx fd;k x;k gSA pØokr ds ekxZ vkSj mlds fodkl ij dSu&fÝ’k] csV~l&feyj] xzsy vkSj ,aFksl&dqvks uked pkj diklh izkpyhdj.k Ldheksa rFkk gk¡x&iSu vkSj cdZ FkkWEilu uked nks xzgh; ifjlhek Lrj izkpyhdj.k ¼ih- ch- ,y-½ Ldheks ds izHkko dk v/;;u djus ds fy, iz;ksx fd, x, gSA pØokr dh xfr] U;wure nkc dk fodkl] o"kkZ dk iSVuZ vkSj rkieku ds m/okZ/kj ØkWl lsD’ku ds laca/k esa laosnu’khyrk dh tk¡p dh xbZ gSA ,aFksl&dqvks Ldhe dks NksM+dj vU; lHkh izfr:i.k vfr {kh.k ifjlapj.k ls vfr izpaM pØokrh; rwQku fodflr djus esa l{ke gSaA U;wure dsUnzh; nkc dk cuuk fofHkUu diklh Ldheksa esa vf/kd laosnu’khyrk n’kkZrk gS ftlesa lekdyu vof/k ds 4 fnuksa ds nkSjku dSu&fÝ’k Ldhe ls 966 gS- ik- vkSj ,aFksl&dqvks Ldhe ls 1004 gS- ik- jghA izfr:fir pØokr dh xfr ij fofHkUu diklh izkpyhdj.k Ldheksa dk egRoiw.kZ izHkko jgk gSA blls izkIr gq, ifj.kkeksa ls irk pyk gS fd dSu&fÝ’k vkSj gk¡x&iSu dh feyh tqyh Ldheksa ls pØokr ds U;wure dsUnzh; nkc dk fodkl vkSj iouksa dh {kSfrt ,oa m/okZ/kj lajpukvksa] rkieku folaxfr;ksa vkSj jsucSaM y{k.kksa dks vPNh rjg iznf’kZr fd;k tk ldrk gSA Non-hydrostatic version of Pennsylvania State University- National Center for Atmospheric Research mesoscale model (MM5) is used to simulate the super cyclonic storm that crossed Orissa coast on 29 October, 1999. Experiments are carried out with four cumulus parameterization schemes namely; Kain-Fritsch, Betts-Miller, Grell and Anthes-Kuo and two planetary boundary layer parameterization (PBL) schemes namely; Hong-Pan and Burk-Thompson to study their impact on the movement and development of the cyclone. The sensitivity is examined in terms of movement, evolution of minimum pressure, rainfall pattern and vertical cross section of temperature. All the simulations are able to develop the very severe cyclonic storm from very weak circulation except with Anthes-Kuo scheme. The evolution of the minimum central pressure shows much sensitivity among the different cumulus schemes with Kain-Fritsch producing 966 hPa while Anthes-Kuo 1004 hPa during the 4 days of the integration period. Different cumulus parameterization schemes show significant impact on the simulated movement of the cyclone. The results reveal that the evolution of minimum central pressure and horizontal as well as vertical structures of winds, temperature anomalies and rainband characteristic to a cyclone are well brought out by the combination of Kain-Fritsch and Hong-Pan schemes.